Dolor lumbar crónico, actividad física, riesgo a enfermedades crónicas no transmisibles y estado nutricional en odontólogos de Lima Metropolitana – 2025 - Vasquez Canayo, Linda Melina (2025)
This study aimed to determine the relationship between chronic low back pain and physical activity, the risk of chronic non-communicable diseases, and nutritional status in dentists in Metropolitan Lima. The study was descriptive and correlational, non-experimental, quantitative, and cross-sectional. The sample consisted of 376 dentists under 65 years of age, of both sexes. 19.68% and 12.23% of the dentists evaluated were overweight and obese (Class I), respectively, and both groups also presented with Class III obesity (0.53% and 1.60%). Regarding abdominal circumference, 20.21% presented a high risk and 48.14% a very high risk. In terms of physical activity, 18.88% had low activity levels and 44.41% moderate activity levels. 59.04% presented a risk of hypertension, 57.18% of diabetes, 54.26% of diabetes, and 56.65% of cancer. 52.13% of dentists experience persistent discomfort; 23.4% reported discomfort lasting longer than one month, 41.33% experienced this discomfort during the last 12 months, and 26.02% lost work time due to medical leave. Furthermore, 28.93% and 30.41% considered the pain to be severe and very severe, respectively. A statistically significant relationship was found between chronic low back pain and nutritional status, activity level, and risk of chronic non-communicable diseases.